2020
DOI: 10.1016/j.avsg.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Lockdown Strategy on Vascular Surgery Practice: More Major Amputations than Usual

Abstract: Background: The aim of this study is to investigate the impact of the coronavirus disease 2019 (COVID-19) lockdown period on the number and type of vascular procedures performed in the operating theater. Methods: A total of 38 patients who underwent 46 vascular procedures during the lockdown period of March 16th until April 30th, 2020, were included. The control groups consisted of 29 patients in 2019 and 54 patients in 2018 who underwent 36 and 66 vascular procedures, respectively, in the same time period. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
61
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 10 publications
5
61
2
5
Order By: Relevance
“…Similar to our findings, Schuivens et al observed more amputations during the COVID-19 lockdown as patients presented with more extensive ischemic disease. 17 Unfortunately, this has shown trainees the time-sensitive nature of limb salvage. While the reduction in skills seen with decreased operating room (OR) time can be ameliorated by increased surgical skills labs, 18 the impact of delayed care for patients has an indelible negative consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Schuivens et al observed more amputations during the COVID-19 lockdown as patients presented with more extensive ischemic disease. 17 Unfortunately, this has shown trainees the time-sensitive nature of limb salvage. While the reduction in skills seen with decreased operating room (OR) time can be ameliorated by increased surgical skills labs, 18 the impact of delayed care for patients has an indelible negative consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Actionability of the results emerged from this study should also be seen in the perspective of the future organizational evolution of diabetes care after the emergency of the COVID-19 pandemic, which took place well after this study was conceived and conducted. The disruption of care delivery may translate into an increase in LEA rates [ 42 ]. Furthermore, evidence is emerging that people with T2D are at a higher risk of serious complications due to COVID-19 [ 43 ], potentially presenting an opportunity to regard coordinated remote consultations for preventing infections in the household and primary care centers, while enhancing opportunities for multidisciplinary consultation.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 lock-downs have also affected upstream care of vascular and diabetic patients and resulted in a dramatic increase in the rate of amputations. 2 , 3 Of note, the ARS is particularly useful for the closure of these lower limb amputations, where the rate of wound dehiscence and other complications is over 20%. 4 …”
mentioning
confidence: 99%